The Influence of Baby Massage on the Sleep Quality of Babies Aged 6-7 Months in Percut Village in 2021 - Irka Setiawati; Nova Prihartini; Amenda Paswita Sebayang; Vera Kristina Hulu (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Sleep disorders in babies are a form of problems faced by parents. Baby massage is an alternative effort to help relieve muscle tension so that the baby calms down and falls asleep. This study aims to determine whether there is an effect of infant massage on sleep quality in infants aged 6-7 months in Percut Village, Percut Sei Tuan District, Deli Serdang Regency. This study used an experimental analytic method without a control group using a pre-test and post-test one group design. This research was conducted in Percut Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, Indonesia. When this research was carried out from March 2021 to July 2021. The sampling technique in this study used total sampling, namely by using the entire population as a research sample of 30 babies. The research instrument uses a data collection tool in the form of a questionnaire. Data analysis used the Paired Sample T-Test using a computer device, namely Statistical Package For The Social Science (SPSS 16). The results of the study are that there is a significant effect between baby massage on the sleep quality of babies aged 6-7 months in Percut Village, Percut Sei Tuan District, Deli Serdang Regency, with p-value = <0.001 (α<0.05). Based on these results, it is recommended for health service workers to motivate parents to massage their babies regularly, especially for nurses to be more professional and skilled in the field of baby care and increase collaboration with other medical personnel in carrying out health education among the wider community about the benefits of baby massage. on sleep quality in infants.Keywords : Baby Massage, Infant, Sleep Quality